SGD1, a key enzyme in tocopherol biosynthesis, is essential for plant development and cold tolerance in rice. (July 2017) - Wang, Di; Wang, Yunlong; Long, Wuhua; Niu, Mei; Zhao, Zhigang; Teng, Xuan; Zhu, Xiaopin; Zhu, Jianping; Hao, Yuanyuan; Wang, Yongfei; Liu, Yi; Jiang, Ling; et al.
Highlights: sgd1-1 and sgd1-2 display dwarf and small grain phenotypes. SGD1 encodes a homogentisate phytyltransferase and is essential for tocopherol biosynthesis. Tocopherols are not major antioxidants under normal conditions in rice. Tocopherols are essential for cold resistance in rice. Abstract: Tocopherols, a group of Vitamin E compounds, are essential components of the human diet. In contrast to well documented roles in animals, the functions of tocopherols in plants are less understood. In this study, we characterized two allelic rice dwarf mutant lines designated sgd1-1 and sgd1-2 ( small grain and dwarf1 ). Histological observations showed that the dwarf phenotypes were mainly due to cell elongation defects. A map-based cloning strategy and subsequent complementation test showed that SGD1 encodes homogentisate phytyltransferase (HPT), a key enzyme in tocopherol biosynthesis. Mutation of SGD1 resulted in tocopherol deficiency in both sgd1 mutants. No oxidant damage was detected in the sgd1 mutants. Further analysis showed that sgd1-2 was hypersensitive to cold stress. Our results indicate that SGD1 is essential for plant development and cold tolerance in rice.